Estratificação vertical da comunidade de morcegos (mammalia, chiroptera) em uma área de Mata Atlântica no nordeste do Brasil - Nunes, Hannah Larissa de Figueiredo Loureiro (2013)
The Neotropical bat fauna stands out for presenting a high trophic and morphological diversity, which can comprise around 50% of mammal species associated with forests. Among the factors that could possibly allow the existence of this complex fauna, we highlight: the diversity of feeding strategies, the activity patterns, the seasonal variaton in the composition of bat communities and the vertical stratification. The present study aimed to analyze the vertical structure and composition of the bat fauna in an Atlantic forest area. The study was conducted between the months of april 2012 and march 2013, in the Reserva Biológica Guaribas (Sema 3), municipality of Rio Tinto, Paraiba. Three sample nights were performed monthly, with mist nets armed in the same position, placed in the understory and canopy (about 15 meters high), opened for 12 hours every night. Additionally, were performed active search for refuges and, during the last five months of sampling, we used three mobile mist nets set at the understory, opened for six hours every night. The total amount of sampling effort was 92.092 h.m2. From all methodologies, 1.760 individuals were captured, belonging to four families and 23 species, among wich we highlight the first record of Molossops temminckii for the state of Paraiba. The average estimated bat richness (Chao 1, Jack 1, Jack 2, Bootstrap) was 25.3±1.3 species. We observed the existence of vertical stratification, through multivariate analysis (PERMANOVA), with eight species (Artibeus lituratus, Artibeus planirostris, Cynomops planirostris, Glossophaga soricina, Molossops temminckii, Phyllostomus discolor, Platyrrhinus lineatus e Sturnira lilium) significantly more abundant in the canopy than in understory. No species showed a significant preference toward the understory. Besides the difference in species composition, abundance and richness were higher in the canopy. An analysis of variance showed no significant difference between the species capture time, except for Dermanura cinerea. We also found significant and positive correlations between total richness and abundance of Artibeus planirostris with the average monthly rainfall of the last five years for the city of Rio Tinto.